2020
DOI: 10.15678/eber.2020.080206
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Institutional Environments and Entrepreneurial Intention in Estonia: Mediating Roles of Desirability and Feasibility

Abstract: The objective of the article is to examine the influence of institutional environment on potential future entrepreneurs and the mediating role of perceived desirability and feasibility. Research Design & Methods: On the basis of institutional theory, we applied structural equation modelling to test a model of the relationship between three dimensions of institutional environment (regulatory, cognitive, and normative) and Estonian university students' entrepreneurial intentions through the mediating role of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 41 publications
2
19
1
1
Order By: Relevance
“…The Entrepreneurial intention of an individual is an important factor to be understood to understand the new firm creation process (Arasti, Pasvishe, & Motavaseli, 2012). Two dimensions of the institutional environment namely the normative dimension and regulative dimension show a decisive role in framing an intention towards entrepreneurship among Estonian university students (Wannamakok, Chang, & Täks, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The Entrepreneurial intention of an individual is an important factor to be understood to understand the new firm creation process (Arasti, Pasvishe, & Motavaseli, 2012). Two dimensions of the institutional environment namely the normative dimension and regulative dimension show a decisive role in framing an intention towards entrepreneurship among Estonian university students (Wannamakok, Chang, & Täks, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The authors could identify only a few recent studies about entrepreneurship intentions and the environment in Estonia or Baltic countries. Based on the sample of 265 Estonian university students, Wannamakok et al (2020) found that the institutional environment plays a decisive role in Estonian university students' entrepreneurial intentions, except for the cognitive dimension, which does not exhibit a significant effect on entrepreneurial JEEE 13,5 intentions through perceived desirability. Another study referring to Estonia was made by Kallas (2019).…”
Section: Literature Reviewmentioning
confidence: 93%
“…The focused population was that of PhD students enrolled at the University of Seville in 2020-2021. The use of this type of population has been endorsed in different works (Bazan et al, 2020;Bazkiaei et al, 2020;Neves & Brito, 2020;Roy & Das, 2020;Wannamakok et al, 2020). Harrison and List (2004) observed that a collective of university students is a group with a high potential for innovating in their actions and representation.…”
Section: Sample and Data Collectionmentioning
confidence: 99%